2005
DOI: 10.1016/j.febslet.2005.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Origin, distribution and 3D‐modeling of Gr‐EXPB1, an expansin from the potato cyst nematode Globodera rostochiensis

Abstract: Southern analysis showed that Gr-EXPB1, a functional expansin from the potato cyst nematode Globodera rostochiensis, is member of a multigene family, and EST data suggest expansins to be present in other plant parasitic nematodes as well. Homology modeling predicted that Gr-EXPB1 domain 1 (D1) has a flat b-barrel structure with surface-exposed aromatic rings, whereas the 3D structure of Gr-EXPB1-D2 was remarkably similar to plant expansins. Gr-EXPB1 shows highest sequence similarity to two extracellular protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 28 publications
1
42
0
2
Order By: Relevance
“…In addition, genomic DNA sequences of Bx-EXPBs showed that Bx-EXPBs likey did not originate from endogenous or symbiotic microorganisms. BLAST search and genomic DNA sequence of Bx-EXPBs led to suggestion that Bx-EXPBs could have originated from bacteria via horizontal gene transfer as shown in other cell wall degrading enzymes and biologically functional (Jones et al, 2005;Kudla et al, 2005;Scholl et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, genomic DNA sequences of Bx-EXPBs showed that Bx-EXPBs likey did not originate from endogenous or symbiotic microorganisms. BLAST search and genomic DNA sequence of Bx-EXPBs led to suggestion that Bx-EXPBs could have originated from bacteria via horizontal gene transfer as shown in other cell wall degrading enzymes and biologically functional (Jones et al, 2005;Kudla et al, 2005;Scholl et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The EG45-like domain found in diverse EXP-related proteins (Kudla et al, 2005;Li et al, 2002;Xu et al, 2001) has multiple cysteine/tryptophan residues and conserved HFD amino acid sequence motif. Non-plant EXPs including nematode EXPs may have evolved independently of plant EXPs leading to the different gene structure.…”
Section: Discussionmentioning
confidence: 99%
“…Expansins are ~27 kDa and ~225 aa proteins consisting of two compact domains: the N-terminal, which resembles the catalytic domain of family 45 glycoside hydrolases (GH45); and the C-terminal, which has been reported as a cellulose-binding domain (Yennawar et al, 2006). Expansin genes appear to be highly conserved throughout plant evolution, but proteins remarkably similar to plant expansin sequences have also been found in Dictyostelium discoideum, (Li et al, 2002), nematodes (Qin et al, 2004;Kudla et al, 2005;Fudali et al, 2008), the ascomycete fungi Trichoderma reesii (Saloheimo et al, 1994), mussels (Xu et al, 2001) and the bacterium Bacillus subtilis (Kerff et al, 2008). The expansin-like sequences in bacteria, animals and fungi appear to be restricted to organisms involved in plant pathogenesis or plant cell wall digestion (Li et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the phylum Nematodea, CBMs have been found in secretions of the root knot nematode Meloidogyne incognita (51) and in the soybean cyst nematode Heterodera glycines (65), and recently it was demonstrated that nematodes express expansin during plant feeding (110,159).…”
Section: Introductionmentioning
confidence: 99%